2017
DOI: 10.1161/jaha.116.004725
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Risk of Screening‐Detected Abdominal Aortic Aneurysm in Men

Abstract: BackgroundModifiable lifestyle‐related factors associated with risk of abdominal aortic aneurysm (AAA) are rarely investigated with a prospective design. We aimed to study possible associations among such factors and comorbidities with mean abdominal aortic diameter (AAD) and with risk of AAA among men screened for the disease.Methods and ResultsSelf‐reported lifestyle‐related exposures were assessed at baseline (January 1, 1998) among 14 249 men from the population‐based Cohort of Swedish Men, screened for AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
56
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 37 publications
1
56
1
1
Order By: Relevance
“…Abrogation of this cytokine, in animal models, has demonstrated efficacy in decreasing aneurysm diameter growth. 2 Although several putative autoantigens have been proposed, the true causative antigen has yet to be identified. 3 We think aneurysm initiation can be divided into 2 stages: sensitization followed by chronic inflammation.…”
mentioning
confidence: 99%
“…Abrogation of this cytokine, in animal models, has demonstrated efficacy in decreasing aneurysm diameter growth. 2 Although several putative autoantigens have been proposed, the true causative antigen has yet to be identified. 3 We think aneurysm initiation can be divided into 2 stages: sensitization followed by chronic inflammation.…”
mentioning
confidence: 99%
“…; Stackelberg et al. ). A meta‐analysis of AAA demonstrated that AAA prevalence was high in patients with coronary artery disease (8.4%) (Elkalioubie et al.…”
Section: Introductionmentioning
confidence: 98%
“…; Stackelberg et al. ), the AAA prevalence was still over 1% in men between 65 and 75 years of age (Jacomelli et al. ; Stackelberg et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Izuzetno, može se videti i pri nativnoj radiografiji abdomena ukoliko su zidovi aneurizme izuzetno kalcifikovani [6]. U svetu su sprovedene četiri velike randomizovane, kontrolisane studije na opštoj populaciji, koje su se bavile skriningom AAA u periodu od 1991. do 2004. godine (Čičester studija, Velika Britanija; Zapadnoaustralijska studija u Pertu, Australija; Viborg studija, Danska; MASSmulticentrična skrining studija -Oksford, Portsmut, Vinčester i Sauthempton: Velika Britanija), sa ukupnim brojem obuhvaćene populacije od skoro 140.000 ljudi [7][8][9]. U svim studijama je ultrazvuk (UZ) istaknut kao metoda izbora za rani skrining AAA zbog jednostavnosti izvođenja, niskih troškova, neinvazivnosti, kao i bez upotrebe jonizujućeg zračenja za razliku od MSCTa, sa visokom senzitivnošću i specifičnošću od 97% [6].…”
unclassified